Marketing the e-Business. - Harris, Lisa (Routledge e-business series., 2002)
How to improve marketing effectiveness through electronic means. Looks at the main marketing themes (product, price, promotion, place) and the bigger 'e' considerations, for example legislation, data protection and ethics.